Petrology of granulites from Shillong Plateau in West Garo Hills district, Meghalaya, India - Bhagabaty, B; Mazumdar, AC (Journal of Nepal Geological Society, 2012)
Intercalated and cofolded bands of cordierite + sillimanite ± garnet ± orthopyroxene bearing metapelites and orthopyroxene + clinopyroxene ± hornblende bearing basic granulites constitute locally the granulite facies terrain in the West Garo Hills district in Meghalaya, India. These rocks show the evidences of poly metamorphism indicating the peak events, the pre-S2 granulite facies metamorphism (M2) which was followed by M3 (i.e., syn-S2), the dominant solid-state fabric-forming episode in the area. The last metamorphic phase M4 postdated S2. The earliest metamorphic fabrics so far recognised are the inclusion phases (M1, syn- to post-S1) in M2 porphyroblasts, representing another high-grade metamorphic event, which was erased out due to the subsequent metamorphic episodes. Petrographic investigations of metapelites reveal a prograde P–T path and high-temperature anatexis of rocks before attaining the granulite facies condition (M2) while textural features in basic granulites clearly indicate a prograde path in terms of hornblende breakdown reaction. The geothermobarometric data from the cores of pre-S2 (M2) mineral assemblages indicate that their peak average metamorphic temperatures were 730 and 750 °C for metapelites and basic granulites respectively whereas the pressures were 5.3–5.9 kbars for metapelites. This P–T estimate of the present study is relatively lower than the ‘true peak’ P–T condition of pre- S2 (M2) assemblages, which may have been modified by chemical reequilibration during subsequent stages. The retrograde P–T history is well documented in the rocks of the area. The retrograde P–T path is revealed by the mineral assemblages forming corona on granulite-facies minerals (garnet corona on pyroxene + plagioclase in basic granulites) or restabilisation of Fe +Mn-rich garnet on preexisting post-S2 fabric defined by sillimanite + biotite + quartz in metapelites. The thermobarometric studies on coronitic garnet in basic granulites quantify cooling through 140 °C during the M4 stage with a minimal decrease in pressure by about 0.5 kbars, while metapelites indicate a cooling path by a temperature decrease of 180 °C for a decrease of 1.0 kbar pressure. Thus, the present study indicates an anticlockwise P–T path formed by the M1–M2 prograde stage and M3–M4 retrograde stage, and thereby implying that the granulite facies metamorphism was caused by magmatic underplating beneath the continental crust. Jour. Nep. Geol. Soc., Vol. 37, 2008, 1-10